Imobilização de uma peroxidase de raízes de Moringa oleífera LAM. (MoPOX) em esferas de quitosana e seu potencial na degradação de corantes têxteis - Lopes, Larissa Alves (2019)
The textile industry is one of the most profitable sectors in the world economy, with Brazil playing a leading role in that scenario. However, the industrial sector is also responsible for the generation of environmental problems, especially with regard to the discharge of effluents with high pollution load, particularly rich in textile dyes. In this context, there is a need for methods that are able to degrade these compounds, for example, through the use of enzymes. Within the existing classes of enzymes, oxidoreductases such as peroxidases have been used in the bioremediation of textile effluents. A class III peroxidase purified from Moringa oleifera roots and denominated MoPOX was immobilized onto glutaraldehyde activated chitosan beads by crosslinking and used for textile dye decolorization. Scanning electron microscopy was used to characterize MoPOX immobilization. Immobilized MoPOX was also characterized for parameters such as optimum pH and temperature, thermo stability, effect of inhibitors, effect of metal ions and substrate specificity. The results showed that the optimum pH was 5.2, the same value found for the free enzyme. The optimum temperature for immobilized MoPOX was 30 ºC, which was different from the value for free enzyme (70 ºC), and the immobilized enzyme presented a higher thermo stability. The apparent kinetic constant value (Km) of immobilized MoPOX was 14.67 mM, lower than that for free MoPOX. The immobilized enzyme was also highly inhibited in the presence of DTT and has broad substrate specificity, as observed for free enzyme. The activity of immobilized MoPOX decreased in inspite of free MoPOX, and could retain 40% residual activity after 5 consecutive cycles. The potential for decolorization was increased after immobilization. For the textile dyes Telon® Turquoise M-5G 85%, Red Astrazon®, Remazol® blue, Remazol® navy RGB and Levafix® orange the decolorization rates using free enzyme were 60%, 14%, 65%, 26% and 10%, respectively. These rates were increased to 80%, 38%, 83%, 82.5% and 65% when using immobilized MoPOX. MoPOX showed no toxicity towards Artemia salina nauplii. The results indicate a promising use of immobilized MoPOX as a bioremediation agent.